Proton and Calcium-Gated Ionic Mesochannels: Phosphate-Bearing Polymer Brushes Hosted in Mesoporous Thin Films As Biomimetic Interfacial Architectures - Brunsen, Annette (2012)
Rational construction of interfaces based on multicomponent responsive systems in which molecular transport is mediated by structures of nanoscale dimensions has become a very fertile research area in biomimetic supramolecular chemistry. Herein, we describe the creation of hybrid mesostructured interfaces with reversible gate-like transport properties that can be controlled by chemical inputs, such as protons or calcium ions. This was accomplished by taking advantage of the surface-initiated polymerization of 2-(methacryloyloxy)ethyl phosphate (MEP) monomer units into and onto mesoporous silica thin films. In this way, phosphate-bearing polymer brushes were used as “gatekeepers” located not only on the outer surface of mesoporous thin films but also in the inner environment of the porous scaffold. Pore-confined PMEP brushes respond to the external triggering chemical signals not only by altering their physicochemical properties but also by switching the transport properties of the mesoporous film. The ion-gate response/operation was based on the protonation and/or chelation of phosphate monomer units in which the polymer brush works as an off-on switch in response to the presence of protons or Ca2+ ions. The hybrid meso-architectured interface and their functional features were studied by a combination of experimental techniques including ellipso-porosimetry, cyclic voltammetry, X-ray reflectivity, grazing incidence small-angle X-ray scattering, X-ray photoelectron spectroscopy, and in situ atomic force microscopy. In this context, we believe that the integration of stimuli-responsive polymer brushes into nanoscopic supramolecular architectures would provide new routes toward multifunctional biomimetic nanosystems displaying transport properties similar to those encountered in biological ligand-gated ion channels.